Planting. Time Impact on Growth of Sap-lingsfP-lari.tH:~ts of ]ojoba (Simmondsia chinensis) - Bashir, Muhammad Azhar; Anjum, Mahammad Akbar; Ahmad, Mustaq (Annals of Arid Zone, 2016)
Jojoba saplings established through rooted cuttings from female plants of promising six strains (PKJ-l, PKJ-2, PKJ-3, PKJ-4, PKJ-5 and PKJ-6) were transplanted in~he field of Jojoba Research Station, Bahawalpur, in October and March during 2003-2005.Th saplings planted in October, resulted in higher survival! increased plaf,lt height, higher mber of branches and leaves per branch than that planted in March~ Saplings;Of PKJ-3 strain had the highest survival, maximum plant height, number of branches an~ number1 f leaves per branch. The interactions between time of planting and strains wer~ non-sig ficant for all parameters except plant height. The saplings of PKJ-3 PIa.nted in. Cj>ctober,att ined the maximum plant height. Another study showed that the survival of tissue-culture plantlets in field conditions was independent of the tirlle of planting and jojbba strain . K.y won!" CIon •• , cuttiogs, geootypos, growth, jojob" pl •• tlotS, '"plings, s;mmond'''j chinensis.